An Instructional Approch To Computer Assisted Language Learning Enhaced Classroom Activities Based On Commuity Language Learning - M, Devendran; T, Ananthi; S K, Premkishor; Dawson, Sam; Charumathy, T.; R, Manimuthukumar (Journal of Neonatal Surgery, 2025)
Advancements in science and technology often have a profound and widespread impact, bringing revolutionary changes to many fields. Recently, developments in Information and Communication Technology (ICT) have significantly transformed the way education is delivered. English Language Teaching (ELT) has particularly benefited from these advancements, gaining new teaching aids and tools. This progress led to the emergence of a discipline known as Computer Assisted Language Learning and Teaching (CALL/CALT) in the latter half of the twentieth century, which has since become well established. As CALL continues to evolve, there is a high demand for research to address various emerging challenges. This article focuses on CALL, aiming to explore the potential for designing CALL-enhanced classroom activities within an existing curriculum.